Characterization of the complete chloroplast genome of an aquatic plant, Sparganium stoloniferum subsp. choui (Typhaceae) - Lei Huang; Qiaoyu Zhang; Xinwei Xu (Mitochondrial DNA. Part B. Resources, 2021)
Sparganium stoloniferum subsp. choui is an aquatic perennial herb distributed in Northeast China. It was published as a new species in 1992 and recognized as a subspecies of S. stoloniferum in Flora of China in 2010. The complete chloroplast genome of S. stoloniferum subsp. choui was sequenced and assembled. The genome size was 161,865 bp in length with 36.8% GC content. Its quadripartite structure consisted of the large single copy (LSC, 88,953 bp) and small single copy (SSC, 19,098 bp) regions, separated by a pair of inverted repeats (IRs) of 26,907 bp. The genome contained 114 distinct genes, including 80 protein-coding genes, 30 tRNA genes, and four rRNA genes. The phylogenetic analysis including four Sparganium species showed that two subspecies of S. stoloniferum were not monophyletic, supporting the resurrection of S. choui as a species.